Racial discrimination among women seeking breast cancer care - Lauren J. Oshry; Ruth I. Lederman; Haley Gagnon; Tsion Fikre; Daniel A. Gundersen; Anna C. Revette; Ashley Odai-Afotey; Olga Kantor; Dawn L. Hershman; Katherine D. Crew; Nancy L. Keating; Rachel A. Freedman; et al. (npj Breast Cancer)
Abstract Discrimination can contribute to worse health outcomes, but its prevalence in breast cancer is not well studied. We aimed to understand how women with stage I-III breast cancer faced discrimination in health care and everyday settings through the Everyday Discrimination Scale, cross-sectional survey. 296 women, 178 (60%) Non-Hispanic White (NHW), 76 (26%) Non-Hispanic Black (NHB), and 42 (14%) Hispanic participated. NHB women reported significantly more discrimination in everyday life compared to NHW women (score 20.1 vs 16.1, p < 0.001) and Hispanic women (score 20.1 vs 16.0, p < 0.001). In the health care setting, NHB had statistically more frequent reports of being ignored (23.7% vs. 5.6%), treated with less respect (21.1% vs. 7.3%), and treated with less courtesy (18.7% vs. 6.2%; all P = < 0.001) when compared to NHW women. NHB women experience a higher degree of discrimination both inside and outside of health care. Further research to understand discrimination on breast cancer outcomes is warranted.